Pengaruh Pengembangan Edukasi Power Point Terhadap Tingkat Pengetahuan Pemeliharaan Kesehatan Gigi Pada Siswa Kelas 3 SDN Leles 02 Kabupaten Garut - Amanda, Anne Amanda; Fatikhah , Nurul; Octaviana, Devy; Widyastuti , Tri (Poltekkes Kemenkes Bandung, 2024)
Dental and oral health is often ignored by people, resulting in various dental and oral diseases. One of the factors that influences this is a lack of knowledge about maintaining oral health. Efforts to maintain healthy teeth and mouth must be made from early childhood. The right media to provide this education is using Power Point. The aim of this research is to determine the effect of developing power point educational media on the level of knowledge of dental and oral health maintenance in class 3 at SDN Leles 02, Garut Regency.The method in this research uses quantitative methods. The type of research used is pre-experimental with a one group pre test post test design. Samples were taken using a total sampling technique with a sample size of 30 respondents. The data analysis technique uses the Wilcoxon test. The results of the study show a p value = 0.000, meaning there is a significant influence between before and after being given education regarding maintaining oral health using power point media. Providing education using PowerPoint is effective for children in increasing knowledge of maintaining oral health.